Representasi Paradoks dan Harmoni Dalam Berkarya - Cucu Retno Yuningsih; Fahmy Al Ghiffary; Dyah Ayu Sintowoko (JURNAL RUPA, 2021)
Abstract. The current study focuses on representation about visual artwork regarding its value of paradoxes and harmony. We use material object which is strongly contradictive as usual to get a unique aesthetic value through compotition, harmony, and color in paiting. The present study also uses descriptive qualitative method to analyze the value of human internal organs as a big topic of painting. Result shows that representational mimesis is closely related to the paradoxical context that is arranged in harmony between one field and another with consideration of aesthetic values. Also, succesfull work in this study is strongly linked with ideas (human’s organ) and visual (painting) which creates a perception of beauty regarding human’s organ as an inspiration of artworks.